1987
DOI: 10.1090/s0002-9939-1987-0866435-1
|View full text |Cite
|
Sign up to set email alerts
|

On the essential numerical range of a generalized derivation

Abstract: Abstract.Let A and B be bounded operators on Hubert spaces Jf and ¿£, respectively. The essential numerical range of the operator X -» A X -XB, defined on the Hilbert-Schmidt class f>1(¿¿?, JÍ?) is expressed in terms of the numerical and the essential numerical ranges of A and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…One may see [2,3,6,7,13,18,20,21,26,27,30,32,36,37] for many interesting results on W e (A) and W e (A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One may see [2,3,6,7,13,18,20,21,26,27,30,32,36,37] for many interesting results on W e (A) and W e (A).…”
mentioning
confidence: 99%
“…This might be the reason why the convexity of W e (A) is seldom discussed for m > 3. In fact, some researchers have studied different geometrical properties of W e (A) under the assumption that W e (A) is convex, and some have examined W e (A) for different classes of operators without discussing their convexity; for example, see [6,26,27,30,32].…”
mentioning
confidence: 99%
“…The famous results on the norms of inner derivation and the generalized derivation as obtained by Stampfli [6] using maximal numerical range have ever since provided a crucial lead in defining of norms of elementary operators.We recall the works of Kyle [9] who examines the relationship between the numerical range of an inner derivation, and that of its implementing element. In his paper, Magajna [2] gives the essential numerical range of the the generalized derivation defined on the Hilbert-Schmidt class in terms of the numerical and the essential numerical ranges of the implementing operators. Shaw [10] in particular, established that the algebra numerical range of a generalized derivation restricted to a norm ideal J is equal to the difference of the algebra numerical ranges of the implementing operators provided that J contains all finite rank operators and is suitably normed .…”
Section: Norm Idealsmentioning
confidence: 99%
“…The essential numerical range of the restriction of a generalized derivation to the class of Hilbert-Schmidt has been computed in [7], by B. Magajna. He has shown that…”
Section: Theorem 22 Let H K Be Two Separable Hilbert Spaces Andmentioning
confidence: 99%
“…Up to now, their spectra and their essential spectra have been characterized; see [4,5,3]. In [7], B. Magajna has determined the essential numerical range of the restriction of a generalized derivation to the class of Hilbert-Schmidt.…”
Section: Introduction Let L(h)mentioning
confidence: 99%